On the classification and bifurcation of multigerms of maps from surfaces to 3-space - Hobbs, C. A.; Kirk, N. P. (Mathematica Scandinavica, 2001)
The A-classification of multigerm singularities is discussed, based on the theory of complete transversals. An A-classification of r-multigerms from the plane to 3-space of A-codimension ≤ 6-r is carried out and the bifurcation geometry of these singularities analysed. This work has applications to the study of two-dimensional spatial motions, giving local models for the singularities which appear on general trajectories of rigid body motions from the plane to 3-space. In addition, our classification is extensive enough to give the full list of simple multigerm singularities from the plane to 3-space.